2022
DOI: 10.1093/tas/txac132
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fenugreek seed extract improves dry matter intake, apparent total tract nutrient digestibility, and alters whole blood transcriptome of Holstein dairy heifers

Abstract: This study was conducted to evaluate the effects of dietary supplementation of a fenugreek seed extract (SAP) as a source of saponins on dry matter intake, blood metabolites, apparent total-tract nutrient digestibility, and whole blood transcriptome of Holstein dairy heifers. Eight (8) heifers (BW = 477 ± 23.8 kg) were stratified by BW and then randomly assigned to 1 of 2 treatments in a cross-over design with two 35-day experimental periods and a 14-d wash-out between the two periods. The heifers were housed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Positive effects of saponins or saponins-containing plants on nutrient digestibility were reported [ 13 , 35 , 68 ]. Kim et al [ 30 ] showed increased in vitro DM degradability and insignificant effects on NDF and protein degradability with the administration of A. saponaria .…”
Section: Effects Of Saponins On Feed Digestion and Rumen Fermentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Positive effects of saponins or saponins-containing plants on nutrient digestibility were reported [ 13 , 35 , 68 ]. Kim et al [ 30 ] showed increased in vitro DM degradability and insignificant effects on NDF and protein degradability with the administration of A. saponaria .…”
Section: Effects Of Saponins On Feed Digestion and Rumen Fermentationmentioning
confidence: 99%
“…Liu et al [ 35 ] showed that feeding ewes on diet supplemented with tea saponins at 2 g/ewe/day enhanced the in vivo digestibility of OM, NDF, and ADF. Recently, Taiwo et al [ 68 ], using saponins extracted from fenugreek seed, noted increased DM, CP, NDF, and ADF digestibility in steers. The positive effects of saponins on nutrient digestibility indicate the ability of saponins to alter the site of digestion in the gastrointestinal tract [ 9 ], which possibly improves feed degradation in the rumen.…”
Section: Effects Of Saponins On Feed Digestion and Rumen Fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to COL4A1 and COL4A2, which also affect the digestive function through the regulation of the blood supply to the digestive organs [46]. And similar studies by Taiwo (2002) found that feeding fenugreek seed extract significantly up-regulated the protein metabolism-related genes in the blood of dairy heifers, resulting in improved energy and amino acid metabolisms, as well as an increased feed intake and digestibility [47]. And our enrichment analysis found that these genes were enriched in the digestive system pathways, such as protein digestion and absorption, gastric acid secretion, and pancreatic secretion, which may indicate that the protein digestive function of the controlled environment population improved.…”
Section: Analysis Of the Impact Of Yfps Digestion Functionmentioning
confidence: 85%